Study on the changes in the East Asian precipitation in the mid‐1990s using a high‐resolution global downscaled atmospheric data set. Issue 5 (13th March 2014) - Chang, Eun‐Chul; Yeh, Sang‐Wook; Hong, Song‐You; Kim, Jung‐Eun; Wu, Renguang; Yoshimura, Kei
Abstract A high‐resolution global atmospheric data set (DA126) is used to understand the East Asian summer precipitation variability. It is found that a fine resolution of the DA126 precipitation data is able to reveal the detailed structures of the rainfall variability over East Asia and southern China in comparison with global analysis precipitation data sets such as the Climate Prediction Center Merged Analysis of Precipitation (CMAP). The first two empirical orthogonal functions (EOFs) of the DA126 precipitation data over East Asia accurately reflect a decadal shift in rainfall over southern China in the mid‐1990s. Furthermore, the first EOF‐related precipitation of the DA126 is related to the tropical Pacific sea surface temperature (SST) variability (i.e., El Niño/Southern Oscillation), and the second EOF‐related precipitation is associated with the Indian Ocean SST variability. Consequently, the tropical Pacific and the Indian Ocean SSTs have different associations with the East Asian monsoon precipitation variability. However, it is difficult to find such a relationship in the first two EOFs of the CMAP data set over East Asia. Using the DA126 precipitation data set, our further analysis indicates that warming of both the tropical Pacific and the Indian Ocean causes an increase in the rainfall anomaly over southern China after the mid‐1990s, which results in a decadal shift in the rainfall anomaly after the mid‐1990s. In addition, the first EOF‐related precipitation is associated with both the Pacific‐Japan‐like (PJ‐like) pattern and the Eurasian‐like pattern. In contrast, the second EOF‐related precipitation is only associated with the PJ‐like wave trains from the western Pacific to East Asia.